"Developing That Balance": Preparing and Supporting Special Education Teachers to Work With Paraprofessionals. (May 2019) - Biggs, Elizabeth E.; Gilson, Carly B.; Carter, Erik W.
The prominence of paraprofessionals in the education of students with severe disabilities highlights the importance of ensuring special education teachers provide effective supervision and support. The authors conducted in-depth individual interviews with members of nine educational teams—a total of 22 teachers and paraprofessionals—to identify (a) the competencies they consider important for special education teachers to work effectively with paraprofessionals and (b) their recommendations for equipping teachers to develop these competencies. Participants identified 10 competencies addressing three areas contributing to balanced leadership: knowledge, skills, and dispositions. They also recommended eight avenues for leadership development spanning three broad pathways: university-based preparation, school/district support, and personal development. The authors' findings suggest the need to embed development of these competencies within existing training and support programs for teachers. The authors offer recommendations for future research and practice targeting teacher development in these areas.